Follower and Takeoff Points in Proximity Spaces - Almohammed, Raghad; Jabar , L .A. A. (Iraqi Journal of Science, 2023)
In the present study, the cluster concept was adopted to find points parallel to the cumulative points of any subset in topology cluster proximity spaces. The takeoff set term was given by the researcher to the set of all points. Also, an opposite definition was found for it, which is the follower set. The relation between them was found and their most important properties were highlighted. Through these two sets, new sets were built that are called, f_σ-set ,f_tσ-set ,t_fσ-set ,bushy set, scant set  .